2013
DOI: 10.1007/s00240-013-0597-0
|View full text |Cite
|
Sign up to set email alerts
|

Lithiasis size estimation variability depending on image technical methodology

Abstract: lithiasis >0.5 cm, intact, and visible via simple radiography. A sample of 245 lithiases was obtained, with 87 rejected as they did not fulfill the inclusion criteria. Initially the three main actual diameters of each lithiasis were measured with a calibrator, then a plain X-ray and a CT scan were taken of the samples to determine the surface size in cm(2) for simple radiography; surface size and volume in cm(3) for CT scan, in bone window and soft tissue (Toshiba Aquillion 64, sections of 0.5 mm, 120 Kv, 250 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Both methods are described in the literature [ 5 ], though they are known to provide different measurements. Usually, soft-tissue window settings tend to overestimate stone size, while bone window settings tend to slightly underestimate stone size [ 6 ]. Furthermore, the attenuation is influenced by the size of the measurement area (region of interest) and partial volume effects.…”
Section: Introductionmentioning
confidence: 99%
“…Both methods are described in the literature [ 5 ], though they are known to provide different measurements. Usually, soft-tissue window settings tend to overestimate stone size, while bone window settings tend to slightly underestimate stone size [ 6 ]. Furthermore, the attenuation is influenced by the size of the measurement area (region of interest) and partial volume effects.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors stressed the importance of standardization of making measurements on NCCT images (10). They demonstrated a larger variability for inter-reader (±1.3mm) than intra-reader (26). Narayan et al demonstrated that stone density measurements vary depending on window, plane and ROI technique.…”
Section: Discussionmentioning
confidence: 95%
“…Magnified bone window NCCT should be preferred for urinary stone evaluation due to better image quality for dense objects as it minimizes noise artifacts close to the stone limits (12, 25). In vitro study already demonstrated that soft tissue window overestimates stone size and bone window provides best accuracy (26). Clinically, it was shown that bone window allows a visual distinction between a stent and a stone (28, 29).…”
Section: Discussionmentioning
confidence: 99%
“…There is still significant controversy in size estimation using soft-tissue and bone windows. Argüelles Salido et al [4] whilst comparing actual surface size and bone window CT scan size when using the European Association of Urology formula or scanner software did not find a statistically significant difference. They also noted that measurements in the soft-tissue window tended to significantly overestimate the surface size, whilst the plain radiography underestimated it slightly but significantly.…”
Section: Introductionmentioning
confidence: 94%